Fluorescent probe for specific detection of cysteine in the lipid dense region of cells - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Gonnade, Rajesh G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new cysteine (Cys) specific chemodosimetric reagent (ER-F) is used in imaging of endogenous Cys localized in the lipid dense region of the live Hct116 cells and the release of Cys within HepG2 cells from a drug following a biochemical transformation. A silica surface, modified with ER-F, could be used for quantitative estimation of Cys present in aqueous solution (pH 7.2) and in a human blood plasma (HBP).

FRET-based probe for monitoring pH changes in lipid-dense region of Hct116 cells - Reddy, Upendar G.; Anila, H. A.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Organic Letters, 2015)
A rhodamine conjugate (L) with a pseudo Stokes shift of 165 nm is used for probing changes in solution pH under physiological conditions. This reagent is found to be nontoxic, and the luminescence response could be used for imaging changes in endogenous pH induced by dexamethanose (DMT) in the endoplasmic reticulum.

New imaging reagents for lipid dense regions in live cells and the nucleus in fixed MCF-7 cells - Ramu, Vadde; Ali, Firoj; Taye, Nandaraj; Garai, Bikash; Alam, Aftab; Chattopadhyay, Samit; Das, Amitava (Journal of Materials Chemistry B, 2015)
Two new uracil (U) and 5-flurouracil (5-FU) labeled ruthenium(II)-polypyridyl based cellular imaging reagents are reported. Confocal laser scanning microscopic images with live and paraformaldehyde (PFA) fixed MCF-7 cells are examined using these two low-cytotoxic reagents. Experimental results show that these two complexes, appropriately functionalized with U (1) and 5-FU (2), have specific affinity for the lipid dense regions like the endoplasmic reticulum, cell membrane, and cytoplasmic vacuoles in live MCF-7 cells, and dye internalization in these regions happened following an endocytosis pathway. Interestingly, these two complexes are found to be localized in the nucleus of the PFA fixed cells. For fixed cells, presumably the lipid layer disruption helped in the explicit localization of the complexes 1 and 2 in the cell nucleus through specific interaction with cellular DNA. Poor and non-specific internalization of an analogous model complex 3, without having a U or 5-FU moiety, reveals the definite influence of U or 5-FU as well as the role of lipophilicity of the respective complex 1 and 2 in the cellular internalization process. Apart from these, a large Stokes shift (similar to 160 nm) and an appreciably long lived (MLCT)-M-3 excited state (similar to 320 ns) in aq. buffer medium (pH 7.4) are other key features for complexes 1 and 2. Unlike the common nuclear DNA staining reagents like DAPI, these low-cytotoxic reagents are found to be highly stable towards photo-bleaching upon irradiation with 455 nm at the MLCT band for these complexes.

New turn on Pd2+-specific fluorescence probe and its use as an imaging reagent for cellular uptake in Hct116 cells - Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
A new coumarin-rhodamine conjugate is used as a specific probe for Pd2+ ions and this could even delineate Pd(II) from Pd(0) or Pd(IV) in aqueous buffer medium (pH similar to 7). Laser confocal microscopic studies reveal that efficient cellular internalization of this reagent helps in imaging the cellular uptake of Pd2+ as low as 0.1 ppm in Hct 116 cells. This reagent could even be used for estimation of Pd2+ in human urine samples.

Reagent for specific recognition of cysteine in aqueous buffer and in natural milk: imaging studies, enzymatic reaction and analysis of whey protein - Anila, H. A.; Reddy, Upendar G.; Ali, Firoj; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2015)
We report a new chemodosimetric probe (L) for specific recognition of cysteine (Cys) in aqueous buffer and in whey protein isolated from fresh cow's milk. Using this reagent we could develop a luminescence-based methodology for estimation of Cys released from a commercially available Cys-supplement drug by aminoacylase-1 in live cells.

Specific reagent for Cr(III): imaging cellular uptake of Cr(III) in Hct116 cells and theoretical rationalization - Ali, Firoj; Saha, Sukdeb; Maity, Arunava; Taye, Nandaraj; Si, Mrinal Kanti; Suresh, E.; Ganguly, Bishwajit; Chattopadhyay, Samit; Das, Amitava (Journal of Physical Chemistry B, 2015)
A new rhodamine-based reagent (L-1), trapped inside the micellar structure of biologically benign Triton-X 100, could be used for specific recognition of Cr(III) in aqueous buffer medium having physiological pH. This visible light excitable reagent on selective binding to Cr(III) resulted in a strong fluorescence turn-on response with a maximum at similar to 583 nm and tail of that luminescence band extended until 650 nm, an optical response that is desired for avoiding the cellular autofluorescence. Interference studies confirm that other metal ions do not interfere with the detection process of Cr(III) in aqueous buffer medium having pH 7.2. To examine the nature of binding of Cr(III) to L-1, various spectroscopic studies are performed with the model reagent L-1 which tend to support Cr(III)-eta(2)-olefin pi-interactions involving two olefin bonds in molecular probe L-1. Computational studies are also performed with another model reagent L-M to examine the possibility of such Cr(III)-eta(2)-olefin pi-interactions. Presumably, polar functional groups of the model reagent L-M upon coordination to the Cr(III) center effectively reduce the formal charge on the metal ion and this is further substantiated by results of the theoretical studies. This assembly is found to be cell membrane permeable and shows insignificant toxicity toward live colon cancer cells (Hct116). Confocal laser scanning microscopic studies further revealed that the reagent L-1 could be used as an imaging reagent for detection of cellular uptake of Cr(III) in pure aqueous buffer medium by Hct116 cells. Examples of a specific reagent for paramagnetic Cr(III) with luminescence ON response are scanty in the contemporary literature. This ligand design helped us in achieving the turn on response by utilizing the conversion from spirolactam to an acyclic xanthene form on coordination to Cr(III).

Tuning of multiple luminescence outputs and white-light emission from a single gelator molecule through an ESIPT coupled AIEE process - Maity, Arunava; Ali, Firoj; Agarwalla, Hridesh; Anothumakkool, Bihag; Das, Amitava (Chemical Communications, 2015)
A unique example of an ESIPT coupled AIEE process, associated with a single molecule (1), is utilized for generating multiple luminescent colors (blue-green-white-yellow). The J-aggregated state of 1 forms a luminescent gel in THF and this luminescent property is retained even in the solid state.

Cysteine-specific fluorescent switch for monitoring oxidative stress and quantification of aminoacylase-1 in blood serum - Anila, H. A.; Ali, Firoj; Kushwaha, Shilpi; Taye, Nandaraj; Chattopadhyay, Samit; Das, Amitava (Analytical Chemistry, 2016)

Specific receptor for hydrazine: mapping the in situ release of hydrazine in live cells and in an in vitro enzymatic assay - Ali, Firoj; Anila, H. A.; Taye, Nandaraj; Mogare, Devraj G.; Chattopadhyay, Samit; Das, Amitava (Chemical Communications, 2016)
We report a new chemodosimetric reagent capable of detecting hydrazine in the presence of several other competing amine derivatives and ionic analytes of biological relevance. This reagent has been utilized for real time monitoring of in situ N2H4 release during the metabolism of a crucial tuberculosis drug, isoniazid, in live HepG2 cells. The fluorescence response of the reagent based on its specific reaction with N2H4 is used for developing an in vitro assay for aminoacylase-1.

Super-resolution probe to monitor HNO levels in the endoplasmic reticulum of cells - Ali, Firoj; Sreedharan, Sreejesh; Ashoka, Anila Hoskere; Saeed, Hiwa K.; Smythe, Carl G. W.; Thomas, Jim A.; Das, Amitava (Analytical Chemistry, 2017)
Selective detection of nitroxyl (HNO), which has recently been identified as a reactive nitrogen species, is a challenging task. We report a BODIPY-based luminescence ON reagent for detection of HNO in aqueous solution and in live RAW 264.7 cells, based on the soft nucleophilicity of the phosphine oxide functionality toward HNO. The probe shows high selectivity to HNO over other reactive oxygen/nitrogen and sulfur species. Luminescence properties of the BODIPY-based chemodosimetric reagent make it an ideal candidate for use as a reagent for super-resolution structured illumination microscopy. The viability of the reagent for biological in vivo imaging application was also confirmed using Artemia as a model.

Fluorescent chemodosimeter for quantification of Cystathionine-y-synthase activity in plant extracts and imaging of endogenous biothiols - Agarwalla, Hridesh; Hoskere, Anila A.; Ali, Firoj; Pradhan, Swaraj Rashmi; Ganguly, Bishwajit; Pramanik, Sumit kumar; Das, Amitava (Chemical Communications, 2018)
A new reagent for quantification of CgS in plant extracts using a generalized methodology suitable for recognition of homocysteine (Hcy) with luminescence ON response.

Polysulfide-triggered fluorescent indicator suitable for super-resolution microscopy and application in imaging - Hoskere, Anila A.; Sreedharan, Sreejesh; Ali, Firoj; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
A new physiologically benign and cell membrane permeable BODIPY based molecular probe, MB-S-n, specifically senses intracellular hydrogen polysulfides (H2Sn, n > 1) localized in the endoplasmic reticulum. This reagent is suitable for mapping the intracellular distribution of H2Sn by wide-field as well as super-resolution Structured Illumination Microscopy (SIM).

Tracking HOCl concentrations across cellular organelles in real time using a super resolution microscopy probe - Ali, Firoj; Aute, Sunil; Sreedharan, Sreejesh; Anila, H. A.; Saeed, Hiwa K.; Smythe, Carl G.; Thomas, Jim A.; Das, Amitava (Chemical Communications, 2018)
BODIPY derivative, SF-1, exclusively shows a fluorescence ON response to HOCl and images endogenously generated HOCl in RAW 264.7 macrophages. Widefield and super resolution structured illumination microscopy images confirm localization in the Golgi complex and lysosomes, and hence specifically detects HOCl generated in these organelles. SF-1 is compatible with 3D-SIM imaging of individual cells.